2021
DOI: 10.1002/anie.202112398
|View full text |Cite
|
Sign up to set email alerts
|

Water Splitting by C60‐Supported Vanadium Single Atoms

Abstract: Water splitting is an important source of hydrogen, a promising future carrier for clean and renewable energy. A detailed understanding of the mechanisms of water splitting, catalyzed by supported metal atoms or nanoparticles, is essential to improve the design of efficient catalysts. Here, we report an infrared spectroscopic study of such a water splitting process, assisted by a C60 supported vanadium atom, C60V++H2O→C60VO++H2. We probe both the entrance channel complex C60V+(H2O) and the end product C60VO+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…118,119 Possible promotor effects of the substrate on which catalyst particles are deposited could even be mimicked using for instance fullerenes, as was recently shown for C 60 V + assisted photocatalytic water splitting. 120 An intriguing direction is the use of picosecond IR pulses to initiate the reaction, and study the timeresolved dynamics of such a reaction. Such a study would complete the characterization of the reactive PES, and is now actively being pursued in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…118,119 Possible promotor effects of the substrate on which catalyst particles are deposited could even be mimicked using for instance fullerenes, as was recently shown for C 60 V + assisted photocatalytic water splitting. 120 An intriguing direction is the use of picosecond IR pulses to initiate the reaction, and study the timeresolved dynamics of such a reaction. Such a study would complete the characterization of the reactive PES, and is now actively being pursued in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…118,119 Possible promotor effects of the substrate on which catalyst particles are deposited could even be mimicked using for instance fullerenes, as was recently shown for C60V + assisted photocatalytic water splitting. 120…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2, the metal atoms of hosts always coordinate with the pentagon (η 5 ) of C 60 with much larger electronic density, as same as the V + C 60 single-atom catalyst. 59,60 The shortest distances between the surface of C 60 and the fragments of pyrrole compounds are about 3.40 Å showing clear π characters, which is like the interlayer spacing of graphite, 61 indicating the van der Waals' interaction. On the other hand, the average distance (Table S1) between M and pentagon of C 60 are about 3.00 Å, possibly meaning the n−π interaction and electron transfer.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Fullerenemetal complexes are ideal test benches to check these characteristics in a well-controlled environment. For example, Hou et al have recently shown that a single vanadium atom supported on C 60 can efficiently catalyze the water splitting process to produce H 2 upon infrared (IR) excitation, demonstrating the importance of carbonaceous supports in single atom catalysts [26,27]. IR spectroscopy is a powerful tool to determine structural characteristics of clusters and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the messenger tagging technique was utilized, employing D 2 as tagging molecule. This technique has been well established in the past decades to obtain the vibrational spectra of molecular species via photodissociation [26,31,32]. D 2 -tagged C 60 Rh n + complexes are synthesized by seeding about 0.5% of D 2 into the He carrier gas.…”
mentioning
confidence: 99%